Implementasi Manajemen Kesiswaan dalam Merekrut Data Peserta Didik MA/SMK Dayah Ulumuddin Kota Lhokseumawe - Nurasiah, Nurasiah; Hayati, Cut Intan (Intelektualita: Journal of Education Sciences and Teacher Training, 2023)
Dayah Ulumuddin Kota Lhokseumawe is an educational institution established in 1988 with the aim of establishing primary schools, madrasahs, secondary schools and vocational schools. This dayah focuses on learning Arabic and English, fostering the younger generation to be knowledgeable and devoted. The dayah's student management is designed to support the teaching and learning process well, ensure students become disciplined, and optimize students' potential. Through qualitative research methods, investigated the efforts of student management implementation on student quality. The research findings highlighted the importance of student management in organizing student activities to support the overall learning process. The results show that Dayah Ulumuddin Lhokseumawe City's student management covers various aspects, from the process of recruiting new students to coaching and developing students. It has a variety of programs, including entrance tests, orientation period, class division, student coaching, extracurricular activities, to student recording and reporting. In conclusion, student management at Dayah Ulumuddin Lhokseumawe City has an important role in supporting the learning process and student development. With various programs and principles applied, the dayah strives to provide the best service to students so that they can develop optimally according to their individual potential.